Solitons and Other Solutions for the Generalized KdV–mKdV Equation with Higher-order Nonlinear Terms (Journal of Partial Differential Equations, 2016)
The generalized sub-ODEmethod, the rational (G' ⁄ G)-expansionmethod, the exp-function method and the sine-cosine method are applied for constructing many traveling wave solutions of nonlinear partial differential equations (PDEs). Some illustrative equations are investigated by these methods and many hyperbolic, trigonometric and rational function solutions are found. We apply these methods to obtain the exact solutions for the generalized KdV-mKdV (GKdV-mKdV) equation with higher-order nonlinear terms. The obtained results confirm that the proposed methods are efficient techniques for analytic treatment of a wide variety of nonlinear partial differential equations in mathematical physics. We compare between the results yielding from these methods. Also, a comparison between our new results in this paper and the well-known results are given.
Keywords: Generalized sub-ODE method; rational (G' ⁄ G)-expansion method; exp-function method; sine-cosine method; generalized KdV-mKdV equation with higher-order nonlinear terms; exact solutions; solitary wave solutions